Psychometric properties of the Nomophobia Questionnaire (NMP-Q) in Peruvian adolescents - Figueroa-Quiñones, Joel; Ipanaqué-Zapata, Miguel; Rivera-Lozada, Oriana; Zevallos Mayanga, Giusepi; Gonzales Diaz, Diana (Frontiers in Psychology, 2025)
BackgroundAdolescence and technological devices have a close relationship during this stage in which anxiety about using a cell phone increases when it is not available. The Nomophobia Scale (NMP-Q) is a measure that evaluates anxiety behaviors when being without a mobile phone.ObjectiveTo evaluate the psychometric properties of the Nomophobia Questionnaire (NMP-Q) in Peruvian adolescents.MethodsAn instrumental study was conducted and 900 adolescents of both sexes, between 12 and 17 years old, living in northern, rural, and eastern regions of Peru were evaluated. A confirmatory factor analysis was carried out to determine the structure and the structural invariance of the measures according to age was evaluated and the reliability was estimated by means of the Omega reliability coefficient.ResultsThe four–factor structure composed of 20 items was confirmed with optimal goodness-of-fit indices (CFI = 0.992; TLI = 0.991; SRMR = 0.053; RMSEA = 0.039). The MIMIC models reported invariance for age groups (ΔCFI <0.01, ΔRMSEA <0.015). The omega reliability coefficients ranged between 0.84 and 0.90.”ConclusionThe Peruvian version of the NMP-Q (20 items) has shown adequate psychometric properties to assess nomophobia in the adolescent population.